The Head of Administration Staff Strategy in Student Administration Management at Islamic Senior High School - Ritonga, Elda Nurmawan; Irawati; Setyaningsih, Rini (PT. Cahya Edupreneur Indonesia, 2025)
This research aimed at analyzing the strategies implemented by the head of school administration staff in student administration management at Islamic Senior High School of Khairul Ummah Air Molek. Student administration is one of the important aspects in supporting the success of education, especially in managing student data, archiving documents, and servicing administration effectively. The head of administration staff had a strategic role in ensuring the continuity of the orderly, efficient, and educational standard-compliant administration process. Qualitative approach was used in this research with descriptive method. Interview, observation, and documentation were the techniques of collecting data. The research findings showed that the head of administration staff at Islamic Senior High School of Khairul Ummah implemented various strategies, such as using of information technology for student data management, improving administration. services, and improving internal communication systems. However, there were several challenges faced, including the distance of students homes from schools, the lack of staff skills in digital data management, and ineffective communication between the administration staff and students. Improvement efforts were made by integrating digital technology into the school administration system and improving coordination between related parties.